1990
DOI: 10.1172/jci114940
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of increased gluconeogenesis in noninsulin-dependent diabetes mellitus. Role of alterations in systemic, hepatic, and muscle lactate and alanine metabolism.

Abstract: IntroductionTo assess the mechanisms responsible for increased gluconeogenesis in noninsulin-dependent diabetes mellitus (NIDDM), we infused 13-14Cjlactate, 13-13Cjalanine, and 16-3Hjglucose in 10 postabsorptive NIDDM subjects and in 9 age-and weightmatched nondiabetic volunteers and measured systemic appearance of alanine and lactate, their release from forearm tissues, and their conversion into plasma glucosq (corrected for Krebs cycle carbon exchange). Systemic appearance of lactate and alanine were both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(103 citation statements)
references
References 39 publications
7
95
1
Order By: Relevance
“…They postulated that in obese NIDDM patients there is an intrahepatic mechanism responsible for the increased conversion of glycerol to glucose and suggested that this could be an increase in the levels of fructose 1,6-bisphosphatase. In contrast to glycerol, Consoli et al [44] have shown that although gluconeogenesis from alanine is increased, this is entirely due to an increase in the availability of alanine. Interestingly, however, they found evidence for an increased intracellular conversion of lactate to glucose.…”
Section: Discussionmentioning
confidence: 97%
“…They postulated that in obese NIDDM patients there is an intrahepatic mechanism responsible for the increased conversion of glycerol to glucose and suggested that this could be an increase in the levels of fructose 1,6-bisphosphatase. In contrast to glycerol, Consoli et al [44] have shown that although gluconeogenesis from alanine is increased, this is entirely due to an increase in the availability of alanine. Interestingly, however, they found evidence for an increased intracellular conversion of lactate to glucose.…”
Section: Discussionmentioning
confidence: 97%
“…[6-3 H]glucose specific activities were determined using 4 ml of plasma in duplicate by HPLC (46) with a CV of 0.5%. Plasma [6,6-2 H2]glucose enrichments were determined by gas chromatography-mass spectroscopy (GC-MS) as previously described (14). Plasma lactate, alanine, glycerol, and FFA concentrations were determined by standard microfluorometric assays (36,43,56).…”
Section: Subjectsmentioning
confidence: 99%
“…Likewise in the study by Arthur and colleagues (Meltzer et al, 1986) ALT activity at least twice the upper limit of normal of 43IU/L was found to be more common among diabetics. Increased gluconeogenesis, owing to increased conversion of alanine to glucose, is suggested as important mechanism for the up regulation of ALT enzyme activity in diabetic subjects (Consoli et al, 1990). The mean value of Age, BMI, Fasting sugar, Post prandial sugar and Serum ALT activity in Diabetic and Non diabetic subjects (n=208).…”
Section: Resultsmentioning
confidence: 99%